PERAN CITRA TOKO DALAM MEMEDIASI HUBUNGAN KUALITAS PELAYANAN DENGAN NIAT BELI ULANG - Putra, I Kadek Dicki Darma; Ardani, I Gusti Agung Ketut Sri (E-Jurnal Manajemen; Vol 7 No 5 (2018)DO - 10.24843/EJMUNUD.2018.v07.i05.p17, 2018)
Retail business in Indonesia is growing very rapidly. The presence of small-scale retail outlets will be a threat to large-scale retail companies such as Hypermart. The purpose of this research is to explain the influence of service quality to store image, service quality to re-buy intention, store image to re-buy intention, and store image role in mediating influence of service quality to re-buy intention. This research was conducted on the consumers of Hypermart Mall Bali Galeria domiciled in Denpasar City. The sample size taken as many as 120 people with purposive sampling method. The results of the study found that service quality had a positive and significant effect on store image. The study also found that each variable of service quality and store image significantly positively affects the repurchase intention, in addition to the image of the shop also significantly mediate the relationship of service quality to the intention of buy back. This shows that the better the image of the store and the quality of service provided it will increase the intention of buy back consumers at Hypermart Mall Bali Galeria.